2019
DOI: 10.1101/569707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RhizoVision Crown: An Integrated Hardware and Software Platform for Root Crown Phenotyping

Abstract: 17Root crown phenotyping measures the top portion of crop root systems and can be used for marker-18 assisted breeding, genetic mapping, and understanding how roots influence soil resource 19 acquisition. Several imaging protocols and image analysis programs exist, but they are not 20 optimized for high-throughput, repeatable, and robust root crown phenotyping. The RhizoVision 21 Crown platform integrates an imaging unit, image capture software, and image analysis software 22 that are optimized for reliable… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The challenges associated with evaluating root traits in the eld have hindered the characterisation of the genetic mechanisms regulating root traits. Several new methods have recently been developed for relatively high-throughput and accurate analyses of roots under eld conditions [33]. In this study, shovelomics-based experiments were conducted to evaluate the CRA, CRD, and CRN of 348 inbred lines at maturity in three eld trials.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges associated with evaluating root traits in the eld have hindered the characterisation of the genetic mechanisms regulating root traits. Several new methods have recently been developed for relatively high-throughput and accurate analyses of roots under eld conditions [33]. In this study, shovelomics-based experiments were conducted to evaluate the CRA, CRD, and CRN of 348 inbred lines at maturity in three eld trials.…”
Section: Discussionmentioning
confidence: 99%
“…After the root respiration measurements, roots from each plant were spread in a 5 mm layer of water in transparent acrylic trays and imaged with a flatbed scanner equipped with a transparency unit (Epson Expression 12000XL, Epson America) at a resolution of 600 dpi. Images were analyzed using RhizoVision Explorer version 2.0.2 (Seethepalli & York, 2020) with algorithms described by Seethepalli et al (2020) with the options for image thresholding level, filter noisy components, threshold for root pruning being set at 205 pixel intensity, 0.2 mm 2 , and 1 pixel, respectively. A root diameter threshold of 0.30 mm was used to distinguish axial roots from lateral roots (Figure 1e).…”
Section: Methodsmentioning
confidence: 99%
“…RPF is generally correlated with greater root biomass and branching, but more nuanced interpretations and its relationship with recently tractable architectural measurements have yet to be established. More intricate phenotyping of root system architecture can be performed upon two-dimensional images of either field-excavated root crowns, or young gel-media grown root systems, followed by analysis with specialized software (Le Bot et al, 2010;Lobet et al, 2011;Galkovskyi et al, 2012;Colombi et al, 2015;Das et al, 2015;Symonova et al, 2015;Delory et al, 2018;Seethepalli et al, 2020). Such methods have been used to quantify root system architecture in diverse crops such as maize, wheat, rice, and cowpea (Bucksch et al, 2014;Canè et al, 2014;Burridge et al, 2017;Wedger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By scaling this technique to mapping populations, studies have identified new univariate or multivariate root QTLs, demonstrating the value of high-throughput and high-information-content trait capture for dissection of plant architecture (Topp et al, 2013;Zurek et al, 2015). Other 3D-based solutions include the use of X-ray computed tomography (XRT), which is capable of imaging any plant structure, including roots within soil based upon physical density properties (Mairhofer et al, 2012;Mooney et al, 2012;Bao et al, 2014;Rogers et al, 2016;Duncan et al, 2019;Li et al, 2019;Li et al, 2020;Helliwell et al). While XRT has been applied to plant physiology in some form for nearly two decades, instrument accessibility and technical limitations typically restrict its use to small plant structures, low throughput, and/or limited fields of view.…”
Section: Introductionmentioning
confidence: 99%